The English assassin - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2003)
Sent to Zurich, Switzerland, to restore a painting owned by a reclusive millionaire banker, art expert and sometime Israeli agent Gabriel Allon discovers his would-be employer murdered and finds himself back in the espionage game.